A arte ao serviço do império e das colónias: o contributo de alguns programas expositivos e museológicos para o discurso de legitimação territorial - Carla Alferes Pinto (Midas: Museus e Estudos Interdisciplinares)
The book A Arte Indo-Portuguesa [Indo-Portuguese Art] by Madalena de Cagigal e Silva (1920-1984) was released in 1966. Having appeared in a context of Portuguese national sentiment due to political and diplomatic events that lead to its release, the reconfiguration of the Indo-Portuguese into an artistic category was the corollary of Portugal’s process of affirmation through a narrative that associated the idea of “the heroic deeds of Portuguese discoveries” to artistic objects. Artistic objects were first classified as Indo-Portuguese in 1881 in an exhibition entitled Special Loan Exhibition of Spanish and Portuguese Ornamental Art (1881) held in London at the South Kensington Museum. Having been brought to Portugal, further used, and criticized the ethnic adjectivisation continued to be associated to the decorative arts until its use was expanded to sculpture, in an exhibition at the Museu Nacional de Arte Antiga (Lisbon) in 1947. Widely dominant both in terms of the number of items and of the time and space it covered, Indo-Portuguese was associated from very early on with the exhibition and museum programmes that built the narrative of a “Portuguese art”, even if produced in a non-European context. Along with other objects, the Indo-Portuguese ones, contributed to the consolidation of an idea of exceptionality, a sense of historical and identity precedent in transoceanic territories of India and Africa, lasting well beyond the 1960s. The aim in this paper was to rebuild the process of acceptance and affirmation of the Indo-Portuguese in the context of the work developed by national museums, and at the same time analyze the discourse and objects selected for international exhibitions, which had as background the political and artistic representation of Portugal abroad.